2014
DOI: 10.1111/jopr.12109
|View full text |Cite
|
Sign up to set email alerts
|

Agreement of Try‐In Pastes and the Corresponding Luting Composites on the Final Color of Ceramic Veneers

Abstract: Luting composites could slightly modify the final color of ceramic veneers. Color matching of a try-in paste to the corresponding luting composite was not always achieved in the 0.7 or 0.5 mm thicknesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 20 publications
4
34
0
8
Order By: Relevance
“…The results obtained for ΔE 0 and ΔE 1 were compared with the 14 groups and in most groups, color correspondence was observed between try‐in paste and resin cement polymerized under the ceramic laminate veneers. This finding does not coincide with the results reported by other authors, since they demonstrated that in most cases, the color of the try‐in paste did not correspond to the color of its respective cement; however, in these previous studies the variation in color did not reach four shades, different ceramic thicknesses were not tested, and in some of them the ceramic veneers were up to 1.0 mm thick. In contrast, the results found by Xing et al corroborate the present finding, given that in general, no difference was observed between the color of the try‐in pastes and their respective cements, although they used ceromer veneers instead of ceramic veneers.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The results obtained for ΔE 0 and ΔE 1 were compared with the 14 groups and in most groups, color correspondence was observed between try‐in paste and resin cement polymerized under the ceramic laminate veneers. This finding does not coincide with the results reported by other authors, since they demonstrated that in most cases, the color of the try‐in paste did not correspond to the color of its respective cement; however, in these previous studies the variation in color did not reach four shades, different ceramic thicknesses were not tested, and in some of them the ceramic veneers were up to 1.0 mm thick. In contrast, the results found by Xing et al corroborate the present finding, given that in general, no difference was observed between the color of the try‐in pastes and their respective cements, although they used ceromer veneers instead of ceramic veneers.…”
Section: Discussionsupporting
confidence: 83%
“…Comparing the extreme colors evaluated herein, the mean values both for ΔE 0 and ΔE 1 registered for the groups that represented color –3 (1a and 1b) were lower than those obtained for the groups that represented color +3 (7a and 7b). These findings confirmed that using thinner ceramic veneers, different colors of cement can change the final color of the laminate bonded to the tooth and are in agreement with the findings of Xu et al who reported that ΔE values were significantly affected by colors of luting composite and veneer thickness.…”
Section: Discussionmentioning
confidence: 99%
“…2 This technique allows for less-aggressive tooth removal than full coverage restorations, and demonstrates excellent clinical performance in terms of periodontal reaction and biocompatibility, which favor a healthy gingival response. 1,3,4,5,6 Declaration of Interests: The authors certify that they have no commercial or associative interest that represents a conflict of interest in connection with the manuscript.…”
Section: Introductionmentioning
confidence: 99%
“…7,8,9 The translucency of veneers adds another level of complexity to the shade-matching process because ceramics allow more light to enter and scatter within the material, giving the underlying dental structure a significant influence on the final color. 6,8 Several factors may also affect the final reproduction, including the combination of ceramic shade, thickness and degree of translucency, 10,11,12 the color of the underlying and surrounding hard tissues, the color and thickness of the luting agent, 12,13,14 and the aging process of adhesive systems. 15,16 From an aesthetic point of view, it is essential to gain the approval of the patient before final cementation takes place.…”
Section: Introductionmentioning
confidence: 99%
“…Bazı araştırmacılar deneme pastalarının restorasyonun final rengini doğru yansıttığını savunurken, bazı araştırmacılar ise tam tersini savunmaktadır. 34,35,[42][43][44] Cubas ve ark. ile Chaiyabutr ve ark.nın, rezin simanlarının farklı seramik tipi ve kalınlıklarının, koyu renkli dişler üzerindeki restorasyonun rengi üzerine etkisini değerlendirmek amacıyla yaptık-ları bir çalışmada, opak ve translüsent iki farklı rezin siman ve 1, 1,5 ve 2 mm kalınlığındaki seramikler kullanılmıştır.…”
Section: Konuyla İlgi̇li̇ çAlişmalarunclassified